Analisis Pengaruh Konsumsi Mi Instan dalam Strategi Penghematan Mahasiswa Kos di Sekolah Vokasi IPB University, Kota Bogor, Jawa Barat - Veralianta Br Sebayang; Farelia Amarnita Putri; Kayla Nuzulul Fitri; Sephia Anggira Putri; Irvanly Dominggus Sihombing; Afifah Zahra; Siti Nur Ruqoyah; Tasya Angelita (Journal of Integrated Agribusiness, 2024)
Instant food, such as instant noodles, is highly favored as a substitute for rice. Instant noodles are especially popular among people, particularly students who live in boarding houses, as they save time, money, and are convenient to consume. This aligns well with students' busy lifestyles, as they often choose fast food when they are hungry; this habit has become common for boarding students in their daily lives. This study aims to analyze the influence of instant noodle consumption as a saving strategy for boarding students at the Vocational School of IPB University. A descriptive qualitative and quantitative method was used, with data collected through a survey of 100 boarding students at the Vocational School of IPB University. The study's results indicate that income and expenditure significantly influence the saving strategies of boarding students at the Vocational School of IPB University. Additionally, the questionnaire results were found to be valid and reliable, with Pearson Correlation values for income, expenditure, and savings variables showing an r-value between >0.5 and 0.8, compared to the r-table value of 0.196, and a Cronbach's alpha value of 0.7. Based on the discussion, it can be conclu ded that the questionnaire is both valid and reliable.